Mexican federalism between ideology and facticity - Chaires Zaragoza, Jorge (Ius Comitiãlis, 2021)
From a review of the historical and legal state of the art, this paper analyzes the way in which Mexican constitutionalism has approached the issue of federalism. It is found that despite the fact that most studies on federalism are impregnated with ideological elements that call for greater decentralization, some authors, from a rather factual viewpoint, consider that in some specific issues the unification and homologation of laws and institutions is necessary. However, these positions are stuck in a positivist vision of the nation-state, which does not correspond to the current reality of the Mexican State, where we are witnessing the emergence of regionalist sentiments that are demanding historical vindications that make possible a new relationship with the federal government based on regional pacts.